Species Home-Making in Ecosystems: Toward Place-Based Ecological Metrics of Belonging - Cordell, Susan; Bardwell-Jones, Celia; Ostertag, Rebecca; Uowolo, Amanda; DiManno, Nicole (Frontiers in Ecology and Evolution, 2021)
Globalization has undeniably impacted the Earth’s ecosystems, but it has also influenced how we think about natural systems. Three fourths of the world’s forests are now altered by human activity, which challenges our concepts of native ecosystems. The dichotomies of pristine vs. disturbed as well as our view of native and non-native species, have blurred; allowing us to acknowledge new paradigms about how humans and nature interact. We now understand that the use of militaristic language to define the perceived role of a plant species is holding us back from the fact that novel systems (new combinations of all species) can often provide valuable ecosystem services (i.e., water, carbon, nutrients, cultural, and recreation) for creatures (including humans). In reality, ecosystems exist in a gradient from native to intensely managed – and “non-nativeness” is not always a sign of a species having negative effects. In fact, there are many contemporary examples of non-native species providing critical habitat for endangered species or preventing erosion in human-disturbed watersheds. For example, of the 8,000–10,000 non-native species introduced to Hawai‘i, less than 10% of these are self-sustaining and 90 of those pose a danger to native biota and are considered invasive. In this paper, we explore the native/non-native binary, the impacts of globalization and the political language of invasion through the lens of conservation biology and sociology with a tropical island perspective. This lens gives us the opportunity to offer a place-based approach toward the use of empirical observation of novel species interactions that may help in evaluating management strategies that support biodiversity and ecosystem services. Finally, we offer a first attempt at conceptualizing a site-specific approach to develop “metrics of belonging” within an ecosystem.